Expanding the chemical diversity of spirooxindoles via alkylative pyridine dearomatization - Dai, Chunhui; Liang, Bo; Stephenson, Corey R. J. (Beilstein Journal of Organic Chemistry, 2012)
A mild and practical synthesis of spirooxindole [1,3]oxazino derivatives from N-substituted isatins and 1,3-dicarbonyl compounds with pyridine derivatives is reported. The reactions provided good to excellent yields. Further exploration of the molecular diversity of these compounds is demonstrated through Diels–Alder reactions.
Keywords: chemical diversity; 1,3-dicarbonyl compounds; Diels–Alder reaction; molecular diversity; pyridine dearomatization; spirooxindole